Analysis of source localization algorithms for near field electromagnetic sources - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
In this study is included the analyzing of the estimation performance of the G-ESPRIT method with respect to the Arrival of Angle (AoA). It has been purposed to defining a 'validity region' to the method for successful estimated a source localization parameter. Also, absolute error rate which is provided using the approximated phase term instead of analytical exact phase term is obtained. © 2019 IEEE.
Keywords: G-ESPRIT Method; Inverse Source Localization; Subspace-Based Algorithm